Length-weight relationship of Lingula sp. in Aceh Southern Shore. Issue 1 (February 2021) - Octavina, C; Agustina, S; Sarong, M A; Sari, P H P; Sahidin, A; Razi, N M; Agustiar, M; Sakinah, R; Fazillah, M R
Abstract: The purpose of this study was to determine the growth pattern of Lingula sp. based on its morphometric analysis. The method used in this research is purposive sampling method. he results showed that the number of Lingula sp. less in the Ujong Pancu beach area (66 individuals) when compared to the Syiah Kuala beach area (169 individuals). Based on the weight value of Lingula sp. in the Syiah Kuala area (5, 861-7, 786 g) it was higher than the Ujong Pancu area (0.082-2.007 g), and the length value was higher in the Syiah Kuala coastal area (39.6-49.4 mm) than the Ujong Pancu beach area ( 19.8-29.6 mm). Besides that, from the calculation of the value of length and body weight, it was found that the value of b at both stations was b> 3 (Ujung pancu, b = 1.9568 and Syiah Kuala, b = 2.896) so that the growth pattern of Lingula sp. classified as negative allometric whereas the length growth is faster than body weight, and the water quality factor in the Ujong Pancu beach area and the Syiah Kuala beach masig are within the normal life limits of Lingula sp.